A Case Report of Dramatically Increased Thyroglobulin after Lymph Node Biopsy in Thyroid Carcinoma after Total Thyroidectomy and Radioiodine - Mandana Moosavi; Stuart Kreisman (Case Reports in Endocrinology)
Thyroglobulin (Tg) is an important modality for monitoring patients with thyroid cancers, especially after thyroidectomy followed by radioiodine (RAI). It is also used as a marker for burden of thyroid tissue whether malignant or benign. Although there have been several reports of rising serum Tg transiently after thyroid biopsy in intact glands and following palpation or trauma, there are no reports in the literature of elevation in Tg after biopsy of suspicious lesions in thyroidectomized patients. In this paper we report a fascinating case of a considerable and initially worrying, although ultimately transient, rise in Tg in a patient 2 years after total thyroidectomy and RAI ablation after fine needle aspiration (FNA) of a suspicious thyroid bed nodule that was proven positive.